A Study on Noise Pollution of Gazipur City Corporation - Latif, MB; Islam, MS; Ali, MS (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted in 4 industries, 4 bus stands and 3 hospitals/clinics through interviewing of workers, staffs of the industries and traffic polices, drivers, passersby, road nearest shopkeepers and patients, nurses, staffs, doctors and other peoples of the medical institutes. Environmental multi-function meter was used to measure the noise intensity (dB) as instrumental survey. From the study it was found that in the industrial sector minimum noise level was 84.71 dB and maximum noise level was 105 dB, in the hospitals/clinics minimum noise level was 75 dB and maximum noise level was 89 dB and in the traffic places minimum noise level was 78 dB and maximum noise level was 107 dB which were crossed the standard level of noise. The traffic places, medical institutes and industries of Gazipur City Corporation were in critical condition in the cases of noise pollution. The major causes of noise pollution in industries were using of old machines, lack of engineering controls, lack of knowledge of authority of the industries about the impact of noise pollution, poor maintenance of the tools, building design and lack of noise reducing instruments. Questionnaire survey determined the noise related health impacts on respondents. The common impacts of noise pollution which they suffered from were headache, heart diseases, hypertension and hearing problem. DOI: http://dx.doi.org/10.3329/jesnr.v7i2.22198 J. Environ. Sci. & Natural Resources, 7(2): 17-23 2014